Undrained Deformation Characteristics of Soft Marine Clay Subjected to One-Way Cyclic Loading with Variable Confining Pressure - Lei Sun (Advances in Materials Science and Engineering)
To gain a better understanding of the undrained deformation characteristic of saturated marine clay soil subjected to vehicle cyclic traffic load, a sophisticated dynamic triaxial was used to conduct a variety of undrained one-way compression cyclic experiments with variable confining pressure (VCP) as well as constant confining pressure (CCP). The results indicate that, compared to CCP test results, VCP is helpful to raise the axial resilient modulus (Mr) and restrain the permanent plastic strain (εap) development of the specimens. By normalization analysis of the measured data of Mr and εap, the virtually unique correlation between normalized average resilient modulus, normalized permanent axial strain after 1,000 loading cycles, and normalized mean normal stress is established, respectively, regardless of the values of CSR. Additionally, the VCP influence on εap is quantified and fitted by a power law function, which can be used for subsoil deformation prediction and provides new insights into the mechanics of strain accumulation under undrained cyclic loading conditions.